2012
DOI: 10.4103/2277-9175.100130
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of congenital hypothyroidism in Isfahan: Do familial components have a role?

Abstract: Background:Despite elimination of iodine deficiency, the rates of both permanent and transient congenital hypothyroidism (CH) in our study were higher than the comparable worldwide rates, which emphasize the major role of genetic factors in the pathogenesis of CH and many studies in this regard confirm this possibility.Materials and Methods:In this review, we report all studies that established during CH screening program regarding familial and genetic component of the disease.Results:Although we could not ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(37 reference statements)
1
8
1
Order By: Relevance
“…Previous studies showed that CH patients had larger head circumference especially those with thyroid agenesis, which reached normal value by treatment [38, 39]. In contrast to other studies [38], in the current survey, the head circumference was lower than normal value, and it may be due to that the majority of CH patients in Isfahan were dyshormonogenetic ones [40], or it may be due to proper and early treatment. However it needs more studies for more accurate conclusion.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous studies showed that CH patients had larger head circumference especially those with thyroid agenesis, which reached normal value by treatment [38, 39]. In contrast to other studies [38], in the current survey, the head circumference was lower than normal value, and it may be due to that the majority of CH patients in Isfahan were dyshormonogenetic ones [40], or it may be due to proper and early treatment. However it needs more studies for more accurate conclusion.…”
Section: Discussioncontrasting
confidence: 82%
“…The confirmed CH incidence is 1/1694 in this population. It is known that the incidence of CH could vary significantly from one ethnic group to another (1/370 ( 17 ) to 1/10,000 ( 18 )). Currently, the overall incidence of CH in Chinese population is not known, two previous studies based on populations in Zhejiang and Shanghai provided the incidences for Han Chinese as 1:1678 and 1:3009, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The first screening for CH in in Markazi Province was performed in 2006. According to the national screening program, the prevalence of CH in Iran is higher than global statistics and different prevalence figures are reported in different provinces ( 5 , 6 , 9 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 95%
“…The first screening programs for CH were conducted in North America in 1972 ( 4 ). Studies have suggested that the prevalence of CH appears to be on the increase in many countries due to many factors such as diagnosis of mild cases, increasing maternal age, increasing premature birth, multiple pregnancies and lower cut-off point ( 1 , 5 , 6 , 7 ). In Iran, screening programs for CH were first carried out by Azizi et al ( 8 ) in Tehran in 1987.…”
Section: Introductionmentioning
confidence: 99%